An incandescent metasurface for quasimonochromatic polarized mid-wave infrared emission modulated beyond 10 MHz - Léo Wojszvzyk (Nature Portfolio, 2021)
Incandescent sources are needed for mid-infrared spectroscopy. Here, the authors present a metasurface of nanoheaters that enables fast thermal modulation beyond 10 MHz and emissivity with well controlled emission spectrum and polarization.